I Saw Ramallah: By Mourid Barghouti, Ahdaf Soueif (translator). (American University in Cairo Press, 2001. 184 pages.) (American Journal of Islam and Society, 2001)
I Saw Ramal/ah is about Barghouti's much-awaited journey to hishomeland after thirty years of exile. The book is rich with personalmemories of places, people, towns, events and times both in the past andpresent and is full of humor, laughter, joy, sadness, heartbreak, sacrificeand mourning. Throughout the book, there is a haunting feeling of loss andloneliness as a result of dispossession.The book starts at the bridge between Jordan and Palestine, the verybridge that Barghouti had innocently crossed thirty years ago in order toreach Cairo to continue his studies. When war broke out in 1967, he wasstill in Cairo and could not return. He remembers that day in 1967 veryvividly, since it was to mark the beginning of a new life for him, as all of asudden he was "struck by displacement." One wonders if he would haveremembered the details as intensely were it just another day in his normallife and not a day that would mark the beginning of life as an exile.Barghouti jumps from his present to the past and back, cleverly andsmoothly, revealing a little here and there, and beckoning the reader tohasten eagerly through the pages to discover the rest of the story. After a ...